Ubiquitous Patchiness in Chlorophyll a Concentration in Coastal Archipelago of Baltic Sea - Scheinin, Matias; Asmala, Eero (Frontiers in Marine Science, 2020)
Productivity and trophic status of aquatic systems is traditionally quantified by chlorophyll a measurements. Environmental conditions and ecological interactions cause variability in chlorophyll a abundance. In coastal ecosystems, shallow and complex bathymetry reduce vertical heterogeneity, but promote horizontal heterogeneity. However, coastal monitoring programs and scientific surveys are primarily focused on the vertical dimension, at the expense of horizontal resolution. Here we demonstrate the spatial patchiness of chlorophyll a in coastal waters. We collected horizontally detailed and extensive in situ chlorophyll a data from the coastal Baltic Sea (SW Finland), covering the ice-free season of an annual cycle. Altogether, more than 200,000 observations were recorded by an automated underway measurement system equipped with an optical sensor connected to a flow-through system. We analyzed the spatial heterogeneity of calibrated chlorophyll a data by using multiple statistical approaches, and quantified the chlorophyll a patches using a rolling average filter. We were able to identify patches and quantify their abundance and size for each of the eleven sampling campaigns. On average, 285 patches, ranging from 0.6 to 3142 m in size, were observed on the 830 km sampling transect. The average size of the patches was 237 (95% CI 226–248) m, most patches being between 10–1000 m. Our results show that patches of chlorophyll a can be effectively identified and quantified by modern in situ optical instrumentation. Such information is both theoretically and practically relevant. First, these results increase our understanding of the overall heterogeneity of the coastal environment. Further, they demonstrate the value of knowing the magnitude and occurrence of chlorophyll a patchiness in accurate detection of changes in coastal ecosystems caused by increased inputs of nutrients.